Inflammatory bowel disease: cost-driving factors and impact of cost sharing on outpatient resource utilization. Issue 4 (11th July 2018) - Le, Duy Vu; Gupte, Renuka; Gabriel, Meghan Hufstader; Vaidya, Varun
Abstract: Objectives: (1) To identify the cost-driving factors of health expenditure in inflammatory bowel disease (IBD), (2) to determine the effect of different cost-sharing levels on outpatient visits and (3) to determine the effect of different cost-sharing levels on medication adherence among patients with IBD. Method: This was a retrospective, longitudinal study in which data were collected from 1999 to 2013 using the Medical Expenditure Panel Survey. The study sample included all patients who had IBD, were at least 18 years old, and had insurance. A comprehensive list of demographic factors was assessed to identify cost-driving factors associated with high level of expenditure in IBD. Two logistic regression models were built to examine the association between outpatient cost sharing and number of outpatient visits, and between prescription cost sharing and medication adherence. Statistical significance was evaluated at P < 0.05. Key findings: Significant cost-driving factors included age, body mass index, education, income, quality of life, Charlson Comorbidity Index and region. The study found that low outpatient cost sharing was associated significantly with high level of outpatient visits. However, different levels of prescription cost sharing had no significant relationship with medication adherence. Conclusions: The finding confirms the existence of financial barriers to care in IBD, which may lead to suboptimal outpatient and, thus, the rapid worsening of the diseases. The finding of cost-driving factors allows the identification of high-risk group for high expenditure, which can be used for future cost-saving strategy.